The Beta‑Convergence of the EU-10 Countries and Regions in the Years 2004-2015 - Jarosław Wołkonowski (Comparative Economic Research. Central and Eastern Europe, 2019)
The article analyzes the beta-convergence of the EU-10 countries and the EU-15 for 2004 and 2015 at four levels - the state, NUTS 1, NUTS 2 and NUTS 3. The strongest beta-convergence is at the level of the EU-10 countries; however, the lower the level of the regional unit, the weaker the beta-convergence. At the NUTS 3 level in Poland, Slovenia and Hungary, divergence was found, which means there are convergence and divergence processes.
Keywords: O47; R10; R19; 330; CEE; integration; economic growth; economic beta-convergence